ChemInform Abstract: Direct Synthesis of Chromium Perovskite Oxyhydride with a High Magnetic‐Transition Temperature. Issue 51 (23rd December 2014) - Tassel, Cedric; Goto, Yoshihiro; Kuno, Yoshinori; Hester, James; Green, Mark; Kobayashi, Yoji; Kageyama, Hiroshi
Abstract The novel stoichiometric perovskite SrCrO2H is synthesized by high pressure/high temperature reaction of SrO, Cr2O3, and SrH2 (5 GPa, 1000 °C, 30 min).